2020
DOI: 10.1007/s12035-020-01912-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Structural, Functional, and Pharmacological Sites for Vesicular Glutamate Transporter Regulation

Abstract: Vesicular glutamate transporters (VGLUTs) control quantal size of glutamatergic transmission and have been the center of numerous studies over the past two decades. VGLUTs contain two independent transport modes that facilitate glutamate packaging into synaptic vesicles and phosphate (Pi) ion transport into the synaptic terminal. While a transmembrane proton electrical gradient established by a vacuolar-type ATPase powers vesicular glutamate transport, recent studies indicate that binding sites and flux proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 314 publications
0
28
0
Order By: Relevance
“…The above discrepancy underscores the dose-dependent duality of the effects of MSO. VGLUT1 is the principal vesicular Glu transporter responsible for loading synaptic vesicles with glutamate, and as such a specific marker for the glutamatergic networks [36]. Notably, VGLUT1 is present in all intrinsic glutamatergic types of neurons of hippocampus [59], the structure involved in generation of seizures by pilocarpine and other chemical stimulants [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above discrepancy underscores the dose-dependent duality of the effects of MSO. VGLUT1 is the principal vesicular Glu transporter responsible for loading synaptic vesicles with glutamate, and as such a specific marker for the glutamatergic networks [36]. Notably, VGLUT1 is present in all intrinsic glutamatergic types of neurons of hippocampus [59], the structure involved in generation of seizures by pilocarpine and other chemical stimulants [60].…”
Section: Discussionmentioning
confidence: 99%
“…Having found that MSO in the present setting inhibits [ 3 H]D-Asp release, we begun a search into the mechanism by which MSO interferes with the mechanism of Glu release. Towards this end we measured the expression of VGLUT1, the principal vesicular Glu transporter responsible for loading synaptic vesicles with glutamate [36]. 13 C-enrichment of Glu from labelled glucose was drastically decreased by MSO both after the first (M+2) and the second turnover (M+4) (Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…High glutamate + glutamine levels were shown to correlate with cognitive impairment in many brain disorders associated with glutamatergic abnormalities ( 34 ). The increased glutamate availability suggests activity-dependent vesicular glutamate release of larger quantal size because vesicle glutamate filling levels are dependent on the concentration of cytoplasmic glutamate to be packaged into synaptic vesicles ( 35 ). As excessive glutamate activates ionotropic receptors in extra-synaptic sites and causes neurotoxicity by calcium influx and generation of free radicals including nitric oxide, the sustained elevation of glutamate levels therefore may be a significant part of the pathogenesis of the widespread glutamatergic abnormalities in bipolar disorder ( 36 ).…”
Section: Brain Pyruvate Carboxylation In Bipolar Disordermentioning
confidence: 99%
“…Deletion of each VGLUT gene in mice, as well as other model organisms such as Drosophila , largely silenced glutamatergic transmission, indicating that VGLUTs are essential for brain functions (Fremeau et al, 2004 ; Wojcik et al, 2004 ; Daniels et al, 2006 ). Furthermore, alterations of VGLUT expression, in addition to the expression of plasma membrane glutamate transporters (O’Donovan et al, 2017 ), are associated with a wide range of neurological disorders, such as epilepsy, anxiety and mood disorders, Alzheimer’s disease, Parkinson’s disease, and schizophrenia (summarized in a recent review by Pietrancosta et al, 2020 ). Therefore, mechanisms and regulators of vesicular glutamate transport mediated by VGLUTs offer potential treatment targets for these disorders.…”
Section: Introductionmentioning
confidence: 99%